TableBot: Getting a Handle on Hybrid Collaboration by Negotiating Control of a Tabletop Telepresence Robot - Dybboe, Maja; Ellemose, Johannes; Vastrup, Alexander Langagergaard; Boudouraki, Andriana; Rintel, Sean; Petersen, Marianne Graves; Grønbæk, Jens Emil Sloth; Klokmose, Clemens Nylandsted (NordiCHI 2024, 2024)
Mobile Remote telePresence robots (MRPs) have been explored as a promising approach to strengthen the agency and presence of remote participants in hybrid work settings. Despite the need and interest in how they might better support hybrid collaboration, substantial challenges remain in terms of their price, availability, and successful application in meeting room contexts. In response to these challenges, this paper explores the opportunities for designing lightweight telepresence robots supporting negotiation of control in hybrid meeting contexts. This paper describes a serial Research-through-Design process, exploring three iterations of design and evaluation of TableBot, a novel tabletop telepresence robot. Based on this work, we present the design of TableBot, and articulate the design space of telepresence robots for hybrid meetings in terms of three trade-offs and a framework for analysing telepresence systems regarding negotiation of control.